Protective Effect of Celeriac (Apium graveolens) Leaf Essential Oil on Temperature and Oxygen-Induced Fish Oil Oxidation - KESBİÇ, O (Kastamonu University, 2023)
The purpose of this work was to identify the volatile components of essential oil extracted from Celeriac (Apium graveolens) leaves (CEO) and assess its antioxidant performance during thermal oxidation of fish oil. Steam distillation method and Clavenger apparatus was used to extrat of CEO from fresh leafs. The volatile component analysis revealed that 98.81% of the volatile components in the resulting product could be recognized. Following examination, the principal components of the product were discovered to be Phthalide (3-isobutylidene) and Fenipentol with a concentration of 49.42% and 28.45% respectively. The product's antioxidant activity was tested using a 2,2-diphenyl-1-picrylhydrazyl (DPPH) study. The 50% inhibitory concentration value (IC50) for CEO was discovered to be 30.52 ppm by the study. To test the product's ability to protect fish oil from oxidation, CEO ratios of 0% (CEO0), 0.1% (CEO0.1), 0.5% (CEO0.5), 1% (CEO1), and 3% (CEO3) were added to fish oil, and the experimental groups were subjected to 24 hours of oxidation at 70 °C with continuous ventilation. According to the oxidation investigation, the addition of CEO suppressed fish oil oxidation and significantly reduced the product's oxidation radicals (p
Keywords: Engineering; Mühendislik; Apium graveolens; Essential oil; Volatile compounds; 6. Clean water